Jembrana Regency's Lively Festival As A Representation Of Local Arts, Culture And Tourism In Commemoration Of The 130th Anniversary Of The City Of Negara - Putu Agus Murtono; Ni Made Yeni Dwi Rahayu; Ni Putu Dewi Eka Yanti (Politeknik Internasional Bali, 2025)
The Jembrana Regency Semarak Festival, held to commemorate the 130th anniversary of Negara City, serves as an important platform for showcasing traditional arts, strengthening local identity, and encouraging the development of culture-based tourism. This study aims to analyze the festival's role in representing the arts and culture of the Jembrana community and its role in strengthening local tourism. A qualitative method was used, with interviews conducted with ten informants from the committee, artists, MSMEs, community leaders, and tourists. The data obtained were analyzed through stages of reduction, presentation, and conclusion drawing to obtain a comprehensive picture of the festival's meaning. The results show that the festival plays a role in preserving traditional arts through performances of Jegog, a traditional dance, and Makepung, a symbol of regional identity. Community involvement significantly contributes to maintaining the continuity of traditions while demonstrating a sense of ownership of local culture. Artistic innovation combined with modern elements also provides space for traditions to remain relevant amidst changing times. Furthermore, the festival offers educational value by involving the younger generation in the cultural heritage process. From a tourism perspective, the Semarak Festival has a positive impact on strengthening the destination's image and improving the local economy. Craft exhibitions, culinary bazaars, and the involvement of MSMEs open up new market opportunities while enriching the tourist experience. The 130th anniversary of Kota Negara adds a historical dimension that reinforces the festival's value, giving it the potential to expand the promotion of culture-based tourism at the local and regional levels. The implications of this research lie in the importance of integrating arts and culture with tourism development strategies, which can serve as a reference in designing similar festival models in other regions.